Acid modified H-USY zeolite for efficient catalytic transformation of fructose to 5-hydroxymethyl furfural (biofuel precursor) in methyl isobutyl ketone-water biphasic system - Pande, Ashwini; Niphadkar, Prashant; Pandare, Kiran; Bokade, Vijay (Energy Fuels, 2018)
Sustainable process and efficient heterogeneous acid catalyst for the preparation of platform chemicals like 5-hydroxymethyl furfural (5-HMF) from renewable source is much in demand in the context of heterogeneous catalysis. Commercially available solid acid catalyst, H-USY zeolite was modified by treating with aqueous solution of H3PO4 and H2SO4 (10–30 wt %). Modified H-USY was completely characterized by XRD, NH3-TPD, energy dispersive analysis X-ray (EDAX), FT-IR, pyridine-IR, and NMR. Its catalytic performance was evaluated for the fructose conversion to 5-HMF in methyl isobutyl ketone (MIBK)–water system. Modified H-USY zeolite was identified to have potential in enhancement of 5-HMF yield up to 65% from 32% (parent H-USY) with minimum formation of furfural (8%). H-USY modified with 10 wt % H3PO4 (10P–Y) was found to be the best compared to other studied catalysts, namely, H-USY modified with 20 and 30 wt % H3PO4 (20 and 30P–Y) or 10–30 wt % H2SO4 (10- to 30S–Y). Best performance of 10P–Y is associated with the optimum combination of moderate acidity (both weak as well as strong), moderate dealumination of Al from extra-framework sites as well as from framework sites of H-USY, formation of new Al–O–P bonds between framework Al and elemental monomeric phosphorus, presence of Brønsted as well as Lewis acidity, and creation of mesopores. This gives new insight on a potential heterogeneous acid catalyst for the synthesis of 5-HMF.

Efficient synergetic combination of H-USY and SnO2 for direct conversion of glucose into ethyl levulinate (Biofuel Additive) - Heda, Jidnyasa; Niphadkar, Prashant; Bokade, Vijay (Energy & Fuels, 2019)
Ethyl levulinate (EL), a biofuel additive for petroleum and biodiesel can also be used as a 100% fuel to replace petroleum diesel with the existing diesel engine. The major problem to make the EL process economical is the lack of a proper conversion technology to convert C-6 sugars such as glucose with higher yield of EL as well as process which can tolerate higher glucose concentration to increase productivity. The present study highlighted the catalytic synthesis of EL from glucose over synergetic combination of zeolite H-USY and Lewis acidic catalysts such as Sn-beta, TiO2, ZrO2, and SnO2. Because of the strong Lewis acidic nature and the subsequent enhancement in the isomerization rate from glucosides to fructosides, the synergetic combination of H-USY with SnO2 showed higher EL yield than the combination with other Lewis acidic catalysts. So far, the highest EL yield of 81% from glucose (50 g/L) at 180 degrees C in 3 h was achieved over the optimal combination of 95% H-USY and 5% SnO2 having strong/weak acidity and B/L ratios of 1.30 and 0.75, respectively. The study was further extended for establishing the proposed reaction mechanism without the formation of 5-hydroxymethyl furfural, levulinic acid, and formic acid which makes the overall process clean and green.

Highly active Brønsted acidic silicon phosphate catalyst for direct conversion of glucose to levulinic acid in MIBK–water biphasic system - Bokade, Vijay; Moondra, Hitakshi; Niphadkar, Prashant (SN Applied Sciences, 2020)
Due to depletion of fossil fuel reserves and environmental concerns demand the utilization of other renewable feedstocks such as biomass which is available abundantly in different quantities throughout the world. Catalytic transformation of this biomass or biomass-derived products such as glucose to valuable platform biochemicals viz: levulinic acid (LA) is academically as well as industrially important reaction. In the present work, Silicon phosphates (SixPO4) catalysts viz: Si10PO4, Si20PO4, Si30PO4, and Si40PO4 having solely Brønsted acidic properties were prepared by wet impregnation of H3PO4 (10–40 wt%) on fumed silica followed by calcination at 550 °C for 10 h. The prepared catalysts were characterized by various techniques such as XRD; NH3-TPD; FTIR etc. Formation of silicon phosphate structure was found to depend on % of P loading and its interaction with silica. The acidic property of SixPO4 catalyst was characterized by NH3-TPD and Pyridine-IR, confirmed that catalyst has exclusively strong Brønsted acidity. A high LA yield of 81 mol% over Si30PO4 has achieved at an optimized reaction condition of 140 °C; 10 h in MIBK–water (9:1) biphasic system.

Highly efficient micro-meso acidic H-USY catalyst for one step conversion of wheat straw to ethyl levulinate (biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Mudliar, Sandeep; Bokade, Vijay (Microporous and Mesoporous Materials, 2020)
Ethyl Levulinate (EL), biofuel additive can blend up to 20% with biodiesel to improve its fuel properties. Till the date, there are reports on homogeneous catalysts (H2SO4, ionic liquid) for synthesis of EL from raw biomass like wheat straw. To best of our knowledge, there is no single report on heterogeneous catalyst for one step synthesis of EL directly from wheat straw. This work is a successful attempt to use heterogeneous micro-meso acidic H-USY (post dealumination and desilication) for direct one step conversion of wheat straw to EL with higher EL yield 24.5 wt%, which is probably the highest so far.
Keywords: Acidity; ethyl levulinate; H-USY; Micro-meso; Wheat straw

Maximization of furanic compounds formation by dehydration and hydrogenation of xylose in one step over SO3-H functionalized H-beta catalyst in alcohol media - Gupta, Anshita; Nandanwar, Sachin U.; Niphadkar, Prashant; Simakova, Irina; Bokade, Vijay (Biomass & Bioenergy, 2020)
Furanic compounds such as furfural (FUR); furfuryl alcohol (F. Alc) are important renewable platform chemicals can be used as such or further convert for preparation of other value added products such as Levulinic acid (LA), Alkyl Levulinates, 2-Methyltetrahydrofuran (MTHF), and Tetrahydrofuran (THF) etc. Sulfonated H-beta zeolite was successfully prepared and used for the synthesis of furanic compounds especially FUR and F. Alc from c-xylose in one step using isopropanol as alcohol media. Prepared catalyst was well characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), BET, NH3-Temperature programmed desorption (TPD) and carbon-hydrogen-nitrogen-sulfur analysis (CHNS). It was found the total acid amount was increased with increase in sulfur loading which confirmed the sulfonic acid group (SO3-H) was successfully grafted onto zeolite structure. 3 wt% H-beta-SO3-H catalyst with optimized reaction parameters of 150 degrees C, 7 h, 25 wt% catalyst loading was tuned to get the highest furanic compound yield of 88.5% (FUR 76.8% + F.Alc 11.7%).The reusability study confirmed that there was a marginal drop of similar to 25% after 3 recycle runs.
Keywords: furfural; Furfuryl alcohol; H-beta; isopropanol; sulfonated zeolite; Xylose

Ozone assisted autohydrolysis of wheat bran enhances xylooligosaccharide production with low generation of inhibitor compounds: a comparative study - Sonkar, Rutuja Murlidhar; Gade, Pravin Savata; Bokade, Vijay; Mudliar, Sandeep N.; Bhatt, Praveena (Bioresource Technology, 2021)
In the present study, ozone assisted autohydrolysis (OAAH) was evaluated for enhanced generation of xylooligosaccharide (XOS) from wheat bran. The total XOS yield with optimum ozone dose of 3% (OAAH-3) was found to be 8.9% (w/w biomass) at 110 degrees C in comparison to 7.96% at 170 degrees C by autohydrolysis (AH) alone. Although, there was no significant difference in oligomeric composition (DP 2-6), significant decrease in degradation products namely furfural (2.78-fold), HMF (3.15-fold), acrylamide (nil) and acetic acid (1.06-fold), was observed with OAAH-3 as a pretreatment option. There was 1-fold higher xylan to XOS conversion and OAAH-hydrolysate had higher DPPH radical scavenging activity than AH. PCA plots indicated clear enhancement in XOS production and lower generation of inhibitors with decrease in treatment temperature. Results of the study therefore suggest OAAH can be an effective pretreatment option that can further be integrated with downstream processing for concentration and purification of XOS.
Keywords: Advanced oxidation; Agro-industry waste; hydrothermal treatment; Ozonolysis; Xylooligosaccharide

Hierarchical TS-1 for epoxidation of non-edible Karanja (Millettia pinnata) oil methyl ester to methyl epoxioleate (biodiesel additive) in presence of H2O2 as oxidizing agent - Anil, Reshma; Niphadkar, Prashant; Bokade, Vijay (Environmental Progress & Sustainable Energy, 2022)
Application of non-edible Karanja (Millettia pinnata) oil which is abundantly available in India is not explored so far. The present study is an attempt to convert fatty acid methyl ester (FAME) obtained from Karanja oil to methyl epoxioleate over hierarchical titanosilicate (TS-1) catalyst. Methyl epoxioleate, a biodiesel additive can blend up to 20% with biodiesels to improve oxidative stability and cold flow properties of biodiesel. A series of hierarchical TS-1 were prepared by desilication of parent TS-1 with 0.1 N NaOH at 80 degrees C for 1, 3, 5, and 7 h, respectively. Samples were characterized by powder XRD, low temperature nitrogen adsorption/desorption, and TEM. Eighty percent FAME conversion with 70% yield of methyl epoxioleate was obtained over 5H-TS-1 catalyst. The enhanced catalytic activity of a 5H-TS-1 compared to parent TS-1 mainly attributed to the high mesoporosity coupled with well-preserved crystallinity. 5H-TS-1 catalyst was found to be completely reusable after calcination at 500 degrees C for 12 h. Hierarchical 5H-TS-1 catalyst for effective conversion of non-edible Karanja oil methyl ester to methyl epoxioleate probably not reported so far.
Keywords: H2O2; hierarchical TS-1; Karanja oil methyl ester; methyl epoxioleate; TS-1

Immobilization of HPW on UiO-66-NH2 MOF as efficient catalyst for synthesis of furfuryl ether and alkyl levulinate as biofuel - Mulik, Nagesh; Bokade, Vijay (Molecular Catalysis, 2022)
Phosphotungustic Acid (HPW) is an inorganic super acid, that is highly soluble in polar solvents limiting its applicability as acid catalysis. To overcome these limitations immobilization of HPW was carried out at room temperature by protonation of-NH2 group of UiO-66-NH2 MOF to UiO-66-NH2-HPW. ATR-FTIR spectroscopy and XPS results confirmed the protonation and chemical interaction between HPW and UiO-66-NH2. STEM-EDS mapping showed homogeneous distribution of HPW on UiO-66-NH2. BET and NH3-TPD confirmed the reduction in specific surface area, total pore volume, and increase in total acidity for UiO-66-NH2-HPW. Further, powder XRD, SEM, and HR-TEM prevailed that there is no change in phase and morphology after post-synthetic modification of UiO-66-NH2. The prepared catalyst is found to be effective for etherification and alcoholysis of furfuryl alcohol (FALc) to Furfuryl ether (FE) and Alkyl levulinate (AL). UiO-66-NH2-HPW has shown 97 mol % FALc conversions in ethanolic media and 31 mol% Ethyl furfuryl ether (EFE) yield and 29 mol% Ethyl lev-ulinate (EL) yield. UiO-66-NH2-HPW is also found to be efficient for the multistep conversion of Furfural (FFR) to FALc, FE, and AL.
Keywords: Alcoholysis; etherification; Immobilization; Phosphotungstic acid; UiO-66-NH2-HPW

Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2023)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment

Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw

One-pot production of liquid hydrocarbons by catalytic hydrodeoxygenation of lignocellulosic biomass using nickel loaded on zeolite-based supports - Siakpebru, Odiri K.; Uchagawkar, Anoop; Gurrala, Lakshmiprasad; Bartlett, Jared; Adamson, Piersen; Gorschak, Nicholas; Hassiba, Adam; Niphadkar, Prashant; Bokade, Vijay; Morais, Ana Rita C. (Energy & Fuels, 2024)
The synthesis of liquid hydrocarbons from lignocellulosic biomass has been achieved with notable success. However, these technologies often require multistep approaches and are energy intensive. Thus, there is a considerable economic and environmental benefit of process intensification by the synthesis of liquid hydrocarbons in a one-pot process. For the first time, we report direct conversion of raw poplar into liquid alkanes and aromatics (carbon yield of 15.6 +/- 0.6 wt %) with high selectivity toward C-7-C15 cycloalkanes (7.8 +/- 0.1 wt %) and low level of oxygenated compounds (<2.0 wt %) at 270 degrees C and 3 MPa initial H(2 )pressure for 6 h using 10% Ni/H-beta zeolite as a catalyst and cyclohexane as a solvent. The effect of temperature (250-270 degrees C), Ni loading (0-10%), and type of zeolite support (H-beta, ZSM-5, and USY) on process performance was also investigated. In addition, the 10% Ni/H-beta catalyst showed recyclability over two reactions, with a 17.6% decrease in liquid hydrocarbon yield after the first reaction. This approach has the potential to simplify the synthesis of liquid fuels from lignocellulosic biomass.

Continuous flow β-zeolite catalysed regioselective alkylation of naphthols using alcohols for synthesis of peroxynaphthalen-2(1H)-one, Azidonaphthalen-2(1H)-one and Fluoronaphthalen-2(1H)-one derivatives - Londhe, Gokul; Bokade, Vijay; Gnanaprakasam, Boopathy (Asian Journal of Organic Chemistry, 2025)
Functionalized naphthols are prominent scaffolds in organic synthesis and materials chemistry. Herein, we demonstrated continuous flow alkylation of alpha- and beta-naphthols by using various primary and secondary benzylic alcohols in the presence of environmentally benign granular beta-zeolite as a reusable catalyst. For a variety of beta-naphthols, the respective alkylated products with good regioselectivity were obtained in high yields under mild reaction conditions. This protocol proceeded via the classical Friedel-Crafts type alkylation process and generated stable carbocations as intermediates. Applying this protocol, versatile naphthol derivatives have been synthesized using primary and secondary benzylic alcohols (50 and 44 examples in batch and continuous flow process, respectively), with good yields. Key advantages of this process includes rapid and efficient transformation, facilitates gram-scale synthesis, and generates water as the sole by-product. The most significant advantage is the continuous reusability of granular beta-zeolite, which further emphasizes the sustainability of the method. The application of alkylated naphthols for quaternary functionalization was demonstrated through peroxidation, azidation, and halogenation reactions under the continuous flow module, which yielded the respective peroxynaphthalen-2(1H)-one, azidonaphthalen-2(1H)-one and fluoronaphthalen2(1H)-one derivatives.
Keywords: continuous flow; Multigram Synthesis; Reusable beta-zeolite; Sustainable Appraoch; Transition metal free